Analisis Kualitas Citra Terhadap Variasi Slice Thickness Pada Pemeriksaan Computed Tomography Scan (CT Scan) Kepala di Rumah Sakit Bhayangkara Makassar - Asnaeni Ansar; Nurfabillah Al Amry; Sultan Hamjar (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2022)
Slice Thickness is the thickness of the image slices on the CT Scan results and is one of the parameters that affect the CT Scan image. This study aims to analyze the image quality of the use of Slice Thickness variations in the CT scan of the head by paying attention to 3 aspects assessed, namely Spatial Resolution, Contrast Resolution, and Noise. This research was conducted by reconstructing the CT scan of the head into 3 types of images, namely Slice Thickness 3 mm, 5 mm, and 7 mm. The results of this study are CT scan images with a slice thickness of 3 mm have an average Spatial Resolution (3.71), Contrast Resolution (3.42), and Noise (3.85) Slice Thickness 5 mm has an average Spatial Resolution (2.71), Contrast Resolution (2.57), and Noise (3.28) and Slice Thickness 7 mm has an average Spatial Resolution (1.57), Contrast Resolution (1.71), and Noise (2 ,14). The best image quality is obtained by using a slice thickness of 3 cm.